PENGARUH SIKAP KEPRIBADIAN (BIG-FIVE PERSONALITY) TERHADAP KINERJA PENYULUH PERTANIAN - Akbardin Akbardin; Sujono Sujono; Muhammad Masri (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
The objective of the study is to examine and analyze the effect of big-five personality affecting the performance of agricultural extension officers simultaneously; to examine and analyze the effect of extroversion, agreeableness, conscientiousness, emotional stability and openness to new experience on the performance of agricultural extension officers in Wakatobi Regency. The unit of analysis of the study was the agricultural extension officers at the Wakatobi Regency Agricultural Service. Respondents who were sampled were 105 officers. Data collection techniques included distributing questionnaires followed by conducting interviews and in-depth documentation. Data analysis was carried out through two stages which were descriptive and quantitative analysis. The analytical method used to examine the hypothesis was multiple linear regression analysis, using SPSS 23.The result of the study indicates that big-five personality has positive and significant effect on the performance of agricultural extension officers in Wakatobi Regency, as well as Extroversion, Agreeableness, Conscientiousness, Emotional Stability and Openness to New Experience having positive and significant effects on the performance of agricultural extension officers in Wakatobi Regency.Keywords: big-five personality; extraversion, agreeableness, conscientiousness, emotional stability and openness to new experience, performance